Inhaled lavender aromatherapy as an effective non-pharmalogical intervention for pain relief in the active phase of labour - Manurung, Monica; Siregar, Nursyahid; Astuti, Dewi Rinda; Jasmawati, Jasmawati (Poltekkes Kemenkes Yogyakarta, 2024)
Labour pain is a physiological process that can cause significant anxiety, tension, and fatigue. Non-pharmacological interventions such as aromatherapy are increasingly considered to manage labour pain with minimal side effects. Lavender essential oil, known for its sedative and anxiolytic properties, has shown promise in reducing pain perception during childbirth. This study aimed to examine the effect of lavender aromatherapy on the level of labour pain among women in the active phase of the first stage of labour. A quasi-experimental study with a pretest-posttest control group design was conducted at Dirgahayu Hospital, Samarinda, Indonesia. A total of 36 women in the active phase of labour were recruited using purposive sampling and assigned to intervention (n = 18) and control (n = 18) groups. The intervention group received lavender aromatherapy via inhalation using a diffuser (4–5 drops of lavender oil in 20 ml of water) for 1 hour, while the control group was instructed in deep breathing relaxation techniques. Labour pain was assessed before and after the intervention using the Numeric Rating Scale (NRS). The intervention group showed a significant reduction in pain scores, from a mean of 6.33 to 5.56 (Mean different = –0.77), while the control group showed a minimal increase from 6.06 to 6.11 (Mean different = +0.05). Statistical analysis using a paired t-test revealed a significant difference in the intervention group (p = 0.001), indicating the effectiveness of lavender aromatherapy in reducing labour pain. Lavender aromatherapy significantly reduced the intensity of labour pain during the active phase of the first stage of labour. This non-invasive and cost-effective intervention can be considered as a complementary method in intrapartum care to enhance maternal comfort and support physiological childbirth.